New species of Radiospongilla (Porifera: Spongillidae) from Brazilian inland waters - Nicacio, Gilberto; Severi, William; Pinheiro, Ulisses (Zootaxa, 2011)
Radiospongilla Penney & Racek, 1968, characterized by gemmoscleres radially arranged on gemmules and absence of microscleres, is widely distributed in the world across all zoogeographical regions except for Antarctica. In the Neotropical Region only two species are known so far: R. crateriformis (Potts, 1882) and R. amazonensis Volkmer-Ribeiro & Maciel, 1983. Here we describe a new species of Radiospongilla, R. inesi sp. nov., from 28 specimens collected between May 2007 to April 2010 from channels and ponds at the Aquaculture Station of Universidade Federal Rural de Pernambuco, Rio do Prata Basin, Recife, Pernambuco State, Brazil. This new species differs from other species of Radiospongilla from South America in the morphology of its megascleres and gemmoscleres.